Activities for Older People in Care Homes : a Handbook for Successful Activity Planning. - Crockett, Sarah (Jessica Kingsley Publishers, 1970)
When tasked with providing activities for older people in care, it can be difficult to know where to begin. What constitutes an activity? How can you make sure activities are positive and person-centred? What can you actually do? Offering advice, encouragement and a wealth of practical suggestions, this is an indispensable companion for carers.